Plant Listing at the National Trust for Scotland (PLANTS) – a large-scale plant collection inventory project - Florence, Anna; Ramsay, Claire (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2026)
The Plant Listing at the National Trust for Scotland (PLANTS) project was a three-year plant collections inventory project that ran from 2022 to 2025 and spanned 35 gardens across Scotland. The project was conceived to deal with a plant-recording backlog and aimed to create an accurate set of plant records held in a centralised database. The gardens were inventoried during the summer months and the data collected input into the National Trust for Scotland plant records database and matched with any existing records over winter. At the end of the project the number of accession records held by the organisation totalled 150,000, representing 77,000 living accessions and 86,000 living collection items.